Biogas upgrading using MSWI bottom ash: An integrated municipal solid waste management. (August 2015) - del Valle-Zermeño, R.; Romero-Güiza, M.S.; Chimenos, J.M.; Formosa, J.; Mata-Alvarez, J.; Astals, S.
Abstract: Biogas upgrading using bottom ash from the incineration of municipal solid waste (MSW) is especially interesting for integrated treatment facilities as it would allow closing a complete loop in MSW management. The aim of this research was to assess the interaction between bottom ash (BA) and biogas from anaerobic digestion with the outlook of upgrading in terms of CO2 and H2 S removal, with particle size and bottom ash aging as the main variables. The finest fraction of fresh bottom ash (FBA) presented the best performance, with a sorption capacity of 30–50 kg CO2 ·t −1 dry FBA. The sorption capacity of weathered bottom ash (WBA) was lower than the recorded for the fresh material. From the results obtained it can be stated that the CO2 absorption capacity of bottom ash mainly relies in the finest fraction because of its larger surface area and higher CaO content. In what respect to H2 S sorption capacity, WBA presented a better performance, with values ranging 3.1–5.2 kg H2 S∙t −1 dry WBA. In addition to the energetic enhancement, the proposed technology also allows an immediate stabilization and reuse of bottom ash as the leaching of heavy metals and metalloids remained under regulatory limits. Graphical abstract: Highlights: Fresh bottom ash (FBA) can have a sorption capacity of 50 kg CO2 t −1 . Sorption capacity mainly relies in surface area and CaO content. Weathered BA presented the best H2 S sorption capacity: 3.1–5.2 kg H2 S t −1 . The process allows immediate stabilization and reuse of these residues. The proposed sustainable process allows a full upgrading of biogas.